Climate variability/change and attitude to adaptation technologies: a pilot study among selected rural farmers’ communities in Nigeria - Ayanlade, Ayansina; Radeny, Maren A.O.; Akin-Onigbinde, Akintomiwa I. (Springer, 2018)
Understanding climate variability and change is essential for designing adaptation policies and strategies to deal with the impacts of climate change on the agricultural sector. This Paper aims at assessing climate variability/change, the perception of rural farmers on climate change and preferred adaptation strategies among the farmers in some selected farming communities in Nigeria. The study thus used both meteorology data and social survey, to examine variability/change in climate and factors determining the adaptation techniques adopts by rural farmers. The results show a relatively uniform temperatures and some seasonal variations in recent years (diurnal range of temperature is about 10 °C) but the rainfall shows much more seasonal variations. The rainfall has relatively undeviating trend from 1981 to 1996 but the trend appears to be upwards from the year 1997 to 2010. About 72.8% participants responded in the affirmative that climate is changing but there appears to be a significant relationship between the length of farming experiences and farmers’ perceptions of climate change adaptation techniques. Water-related (about 53%) and nutrient related (about 52%) technologies appear to have a high preference among the farmers. The major driver that determines farmers’ preference for climate change adaptation techniques is their incomes and experiences.